THERMODYNAMICAL ANALYSIS BY 1^Н NMR OF THE COMPLEXATION OF ETHIDIUM BROMIDE TO A DNA OCTAMER, 5’-d(GpApCpApTpGpTpC), IN AQUEOUS SOLUTION - Pahomov, V. I.; Davies, D. B.; Veselkov, A. N. (Biophysical Bulletin)
The self-association of the self-complementary deoxyoctanucleotide, 5’-d(GpApCpApTpGpTpC), and its complexation with the phenanthridinium drag, ethidium bromide (EB), has been studied by 1 D and 2D 500/600 MHz NMR spectroscopy. 2D homonuclear correlation PMR spectroscopy (TOCSY and NOESY) was used for complete assignment of the non-exchangeable protons of the molecules and for qualitative determination of the preferred binding site(s) of the ligand with the oligonucleotide chain. An NMR analysis has been developed for detenmning the thermodynamical parameters of self-association of the DNA octamer and its multicomponent equilibrium of complex formation with EB in solution. Quantitative determination of the equilibrium constants and thermodynamic parameters (free energy, enthalpy and entropy) of duplex formation of the octamer and its complexation with EB is based on investigation of the dependence of proton chemical shifts of the molecules on temperature and on concentration. The experimental results were interpreted In terms of complexes containing different numbers of drug molecules in the octamer duplex (1:2, 2:2,3:2 and 4:2 complexes). It is also found that (i) the relative amount of each molecular complex depends on the ratio of the initial concentrations of the octamer and drug and on the temperature of solution and (ii) successive binding of drug molecules to the octamer duplex is anti-cooperative. KEY WORDS: deoxyoctanucleotide, ethidium bromide, intercalation, thermodynamic parameters, NMR spectroscopy